Updated evidence of the Naoshuantong capsule against ischemic stroke: a systematic review and meta-analysis of randomized controlled trials - Que, Cuilin; Wei, Yupeng; Yin, Guanxiang; Zhou, Congren; Liu, Zhenhong; Lai, Xinxing; Qin, Mingzhen; Xiong, Xuejiao; Zheng, Xiangyi; Dong, Xinglu; Gao, Ying (Frontiers in Pharmacology, 2024)
Background Stroke is a serious health issue that can result in death or disability, leading to a significant economic strain on society and families. A growing number of studies have shown that the Naoshuantong capsule (NSTC) is beneficial as a treatment for ischemic stroke (IS) in recent years. Our study aims to provide an update on the safety and efficacy of the NSTC in IS patients. Methods We thoroughly searched eight databases to identify suitable randomized controlled trials (RCTs) assessing the effectiveness of the NSTC in the treatment of IS. The National Institute of Health Stroke Scale (NIHSS) for an acute period and modified Rankin Scale (mRS) at 3 months for a non-acute period were considered the primary outcome, and secondary outcomes included the NIHSS for a non-acute period, mRS, Barthel Index (BI), modified Barthel Index (MBI), Stroke-specific Quality of life (SS-QOL), and the recurrence rate of cerebrovascular events. Subsequently, its quality was assessed using the Cochrane risk assessment scale. Statistical analysis was conducted using RevMan 5.3 and Stata 14.0. Results A total of 27 RCTs were included, which involved 3,139 patients. The results showed that the NSTC improved neurological function not only in the acute period (MD = −2.53; 95% CI: −2.91, −2.15; p < 0.00001) but also in the non-acute period (MD = −3.70; 95% CI: −5.82, −1.58; p = 0.0006) and improved the long-term functional outcomes with lower mRS scores (MD = −0.68; 95% CI: −1.09, −0.26; p = 0.001). At the same time, the NSTC decreased the risk of cerebrovascular disease recurrence (RR = 0.43; 95% CI: 0.27, 0.70; p = 0.0006) and increased the quality of life in the acute period (MD = 23.88; 95% CI: 16.63, 31.13; p < 0.00001). Significant disparities in the incidence of adverse events between the NSTC and control groups were not observed. The certainty of evidence was estimated as moderate to very low. Conclusion The NSTC emerges as a potentially efficacious and safe treatment option for IS. NSTC could improve neurological function in different period of IS, and it has certain clinical value in secondary prevention. As a result of the poor quality and heterogeneity of the included trials, larger and standardized RCTs are needed to validate NSTC in IS treatment. Systematic Review Registration: https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=482981, identifier CRD42023482981.